Dipstick Urinalysis Screening of Healthy Neonates - Behnaz Falakaflaki; Seyed Nouraddin Mousavinasab; Saeideh Mazloomzadeh (Elsevier, 2011)
Renal disease may accidentally be discovered during urinalysis. This study was conducted to examine the usefulness of dipstick urinalysis screening in healthy neonates for the diagnosis of underlying renal disease and to study the magnitude of abnormal urinalysis in apparently healthy neonates. Methods: In this descriptive study, voided urine samples were obtained from 400 apparently healthy neonates and tested using urine dipstick. The reaction of dipstick strip was read visually by a trained nurse. In cases with an abnormal urine analysis, a second screen test was performed within a week, and for those with persistent abnormalities, complete diagnostic tests were done. Results: On the first urinalysis, 375 (94%) subjects were normal and 25 (6%) had abnormalities: 23 had proteinuria (5.75%), one was blood positive (0.25%), and one was both protein and blood positive (0.25%). Male neonates had a higher proportion of proteinuria than female neonates (p=0.038). In the second examination, proteinuria was found in five (1.25%) neonates, but the proportion of other abnormalities did not change. In follow-up investigations, ureteropelvic junction obstruction and vesicoureteral reflux were recognized in two infants who had blood-positive or combined blood- and protein-positive results on their first tests. Conclusion: The findings of this study show that dipstick test during neonatal period could be used for early diagnosis of renal diseases.